Age and size related changes in growth of Acer pseudoplatanus and Fraxinus excelsior species - Abdul Hamid, Hazandy; Mencuccini, Maurizio (Academic Journals, 2008)
The aim of this study is to investigate the effects of tree age and tree size on growth characteristics of two broadleaf species by conducting experiments in the field and the glasshouse. Growth characteristics, such as relative growth rate and growth efficiency were measured. Comparisons were established among results observed in the field with the ones obtained in the grafted seedlings. The results showed that relative growth rate and growth efficiency decreased substantially with increasing age of donor trees in the field. In contrast, these parameters seemed almost constant on grafted seedlings, i.e., scions taken from donors with different meristematic ages did not show the age-related trend after they were grafted onto the rootstocks.